DIGITAL TRACES, SOCIAL RESIDUES: USAGE AS SELF-REPRESENTATION ON LIFESTYLE APPS - Butkowski, Chelsea Paige; Bimo, Sara; Bhandari, Aparajita (AoIR Selected Papers of Internet Research, 2023)
Self-representation is ubiquitous in digital spaces, but much of the existing literature discussing it is focused on social media contexts. Self-representation involves the creation of media traces that record users’ presence and existence through media, but these traces and the platforms that circulate them do not have to be explicitly or directly social. We study self-representation in alternative digital contexts: lifestyle apps focused on ambient usage behaviors that are generally private, personal, or invisible in online spaces. These apps incorporate social features based on displays of user data—streams repurposing users’ engagement with the platform as social displays to networked friends. The three apps of interest include the payment app Venmo, music streaming app Spotify, and fitness tracking app Strava. We study these apps through a combination of “walkthroughs” of each of the platforms and interviews with users. Our findings suggest that these platforms repurpose individual user behaviors as digital residues in social streams, transforming them into networked self-representations. Within this process, we expect that some users intentionally mobilize their engagement with the apps as social performances. Ultimately, this study raises questions about digital self-making, commodification, and platform sanctioned sociality beyond social media.